Calculation of Weights for the Regional Network - Kjetil Martinsen; Fredrik Wulfsberg (Norges Bank, 2010)
This memo documents the structure and use of weights for observations from the regional network. With effect from round 3/09, observations from the network have been weighted using a new set of weights that better capture variations in size between sectors and regions and over time. The national and sector averages based on the new weights are nevertheless highly correlated with the averages based on the old weights.
hdl:11250/2507784
Keywords: 330